2017
DOI: 10.5194/acp-2017-931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal variation and chemical characterization of PM<sub>2.5</sub> in northwestern Philippines

Abstract: Abstract. The seasonal and chemical characteristic of fine particulate matter (PM 2.5 ) was investigated in Burgos, Ilocos Norte, located at the northwestern edge of the Philippines. Each 24H-sample of fine aerosol was collected for two weeks every . Three-day wind back trajectory analysis of air mass reveals the influence 5 of the North Western Pacific monsoon regimes on PM 2.5 concentration. During southwest monsoon, sea salt is the dominant component of fine aerosols carried by moist air from the South Chin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Cruz et al (2019) showed with sizeresolved aerosol measurements and positive matrix factorization modeling that five predominant pollution sources during the Southwest Monsoon include aged aerosol, sea salt, combustion, waste processing, and vehicular/resuspended dust. The period of time between November and April coincides with a dry season with more northeasterly winds (Bagtasa et al, 2018;Chang et al, 2005;Cruz et al, 2013;Moron et al, 2009), including influence from both East Asia and local burning activities (Hilario et al, 2020b(Hilario et al, , 2020c 2018). The same set of sources impacting the West Coast generally apply to the East Coast (Hand et al, 2012b(Hand et al, , 2019 with notable features being more influence from African dust (Aldhaif et al, 2020;Zuidema et al, 2019), enhanced agricultural burning (especially in the Southeast) (Sevimoglu and Rogge, 2019;Shingler et al, 2016), and extensive power plant emissions that have actually been reduced over time since the early 1990s leading to SO 4 2 − reductions (Hand et al, 2012a).…”
Section: Islands-maunamentioning
confidence: 99%
“…Cruz et al (2019) showed with sizeresolved aerosol measurements and positive matrix factorization modeling that five predominant pollution sources during the Southwest Monsoon include aged aerosol, sea salt, combustion, waste processing, and vehicular/resuspended dust. The period of time between November and April coincides with a dry season with more northeasterly winds (Bagtasa et al, 2018;Chang et al, 2005;Cruz et al, 2013;Moron et al, 2009), including influence from both East Asia and local burning activities (Hilario et al, 2020b(Hilario et al, , 2020c 2018). The same set of sources impacting the West Coast generally apply to the East Coast (Hand et al, 2012b(Hand et al, , 2019 with notable features being more influence from African dust (Aldhaif et al, 2020;Zuidema et al, 2019), enhanced agricultural burning (especially in the Southeast) (Sevimoglu and Rogge, 2019;Shingler et al, 2016), and extensive power plant emissions that have actually been reduced over time since the early 1990s leading to SO 4 2 − reductions (Hand et al, 2012a).…”
Section: Islands-maunamentioning
confidence: 99%
“…There are many other studies motivated by YMC and addressing YMC issues using data from satellites, global reanalysis products, and numerical models. These studies cover a wide range of topics, such as the diurnal cycle (Baranowski et al, 2019), MJO propagation over the MC (Burleyson et al, 2018; Pang et al, 2018) and its barrier effect (DeMott et al, 2018; Ling et al, 2019), atmospheric waves (Ruppert & Zhang, 2019; Takasuka et al, 2019), aerosol (Bagtasa et al, 2018; Cohen et al, 2018; Koplitz et al, 2018), the monsoon (Diong et al, 2019; Duan et al, 2019), the ITF and the ocean in general (Cao et al, 2019; Gordon et al, 2019; Hu et al, 2019; Liang et al, 2019), and prediction and predictability (Wang et al, 2019).…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Such phenomenon has been addressed by previous literature that long-range transport causes the deterioration of regional air quality in the downwind regions (Chuang et al, 2012). Moreover, interaction of air pollutants may occur in the boundary areas neighboring Taiwan Strait and Bashi Channel (Li et al, 2012;Bagtasa et al, 2018).…”
Section: Introductionmentioning
confidence: 95%